First normative reference of standing long jump indicates gender difference in lower muscular strength of Macedonian school children - Gontarev, Seryozha; Zivkovic, Vujica; Velickovska, Lence A.; Naumovski, Milan (Scientific Research Publishing, Inc., 2014)
Background: This is the first study to publish the normative reference values for assessment of the level of muscular strength through the “standing long jump” test carried out on a large sample of Macedonian school children. The normative values encompass a wide span of years (6 - 18). Methods: The research was realized in a large sample of 12618 school children at the age of 6 to 18 years from Macedonia. The sample was divided in 14 groups, according to chronological age and each age group was divided into two subgroups according to the criteria of gender. For estimation of the morphologic characteristics, the following anthropometric measures have been applied: body height in standing position (cm), body weight (kg), as well as the body mass index (BMI). Children aged 6 or above were invited to take a standing long jump test. Results: Boys show statistically better results in all age categories in the standing long jump test than girls, and these differences become bigger with the increase of age, especially after the 14th year (p < 0.000). Results from the linear regressive analysis show that the constants in predicting the standing long jump are similar both in boys and in girls. However, the age coefficient in boys is two times higher than that in girls. The Body Mass Index, as a factor, influences two times more in boys in predicting the standing long jump, which indicates that the body size in boys has bigger inverse impacts on the results of the standing long jump than that in girls. Conclusion: Normative reference values shall provide proper assessment and interpretation of the level of muscular strength of the Macedonian school children in terms of the age and gender, accurate detection of progress of an individual as well as undertaking preventive measures and level of intervention
Keywords: Fitness Testing; Standing Long Jump; Gender; Children; Adolescents; Lower Muscular Strength